A Bibliometric Review of Contributions from Various Countries and Their Impact on Marketing Strategies and Sales Practices Worldwide - Frans Sudirjo; Ni Komang Mela Tri Utari; Zainal Abidin; Gatot Wijayanto; Arini Novandalina (Eastasouth Institute, 2023)
This bibliometric study provides a comprehensive analysis of global contributions to marketing strategies and sales practices. It maps the geographical distribution of research output, highlighting influential countries like the United States, the United Kingdom, China, India, and Australia. Emerging contributors from Asia and Latin America are fostering international collaborations. Citation networks demonstrate global research impact, while keyword analysis reveals enduring themes and emerging trends. Practical recommendations include emphasizing international collaboration, digital transformation, quality management, SME support, strategic planning, customer satisfaction, and attention to physical evidence in services marketing. This review advances understanding and guides stakeholders in navigating the evolving global landscape of marketing.